Economic Evaluation And Factors Affecting Smoking Cessation Using Istop Program In A Local Manufacturing Company - Goh, Su Lun (2018)
Tobacco products are a double-edged sword. While tobacco products contribute to a country’s economic significantly, it is also a notable risk factor for human health and a silent thief of the wealth of its users, society and nation. Apart from the healthcare cost, the work performance of smokers is also being affected leading to lower productivity. Many studies have also shown that workplace smoking cessation programs are effective and have generated positive savings for the employers. Therefore, workplace smoking cessation has been viewed as a potential strategy to combat the usage of tobacco products. Abundant studies have been carried out abroad, but local studies are scares; especially in the private manufacturing sector. This study was a cross-sectional single prospective cohort workplace smoking cessation study conducted in a local manufacturing company. This study reviewed a 12-week innovative multi-component smoking cessation intervention program to support smoking employees to quit smoking, called “iSTOP” program. The objectives of this study were to evaluate the effectiveness of this innovative program and the smokers’ behaviours as well as to identify factors affecting smoking cessation and relapse. On top of these, the quality of this program was also evaluated using qualitative analysis method, making it more effective in assisting smokers to quit smoking. As this was the Company fully sponsored program, the last section was to calculate the economic return this program to the employer using the common commercial indicators (ROI and IRR), which are familiar by the Management team.